CHANGING PATTERNS IN THE ROLES OF UMUADA IN IGBO SOCIAL FORMATIONS - EMEJULU, Ifeyinwa; UMEAGUDOSI, Mmesoma (Socialscientia: Journal of Social Sciences and Humanities, 2020)
Feminism emanated as a response to the need of finding avenues of helping women all over the world to circumvent the numerous constraints preventing them from contributing maximally to the community and achieving their utmost potentials. It was believed that men were valued more than women and hence enjoyed more opportunities and privileges in the different societies all over the world. While it is so obvious that there are many constraints preventing women from achieving their goals, women are celebrated in Igbo society. The Umuada group which consist of the biological female offspring of a particular kindred plays distinct and powerful roles in their different communities in Igbo land. This group has highlighted the relevance of women in Igbo society. The roles they play include conflict resolution, transmission of culture and serving as agents of social control. In the contemporary society their relevance and contributions have been sustained and even diversified. This study seeks to debunk the belief that women are inferior and are inadequately appreciated in the society by highlighting the unique and incredible roles played by the Umuada group in the traditional and contemporary times. It uses the qualitative approach in evaluating the information derived from primary and secondary sources and does not align itself to any theoretical construct. The study highlights the fact that contrary to wide held belief, women are valued and appreciated in Igbo society.